2021
DOI: 10.1186/s12872-021-01922-w
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effectiveness of position change for patients with pain and vascular complications after transfemoral coronary angiography: a randomized clinical trial

Abstract: Background Prolonged immobilization after transfemoral coronary angiography (TFA) may cause pain and vascular complications in patients. This study aimed to evaluate the effectiveness of a change in position to decrease pain and vascular complications for patients after TFA. Methods This randomized clinical trial was conducted in 2020. Purposive sampling of 72 eligible patients undergoing TFA were selected and randomly assigned to either an experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…A prospective observational study [ 10 ] demonstrated that for patients who received manual compression after TFA, the modified ambulation protocol including 4 h of immobilization and 6 h time in bed was safe and feasible. In addition to reducing ambulation time, changing patients’ position during immobilization was also proposed by previous research [ 3 , 8 , 19 ]. Two studies [ 3 , 19 ] found that position change to a semi-seated position 2 h after TFA is effective and safe to reduce pain without increasing the vascular complications.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A prospective observational study [ 10 ] demonstrated that for patients who received manual compression after TFA, the modified ambulation protocol including 4 h of immobilization and 6 h time in bed was safe and feasible. In addition to reducing ambulation time, changing patients’ position during immobilization was also proposed by previous research [ 3 , 8 , 19 ]. Two studies [ 3 , 19 ] found that position change to a semi-seated position 2 h after TFA is effective and safe to reduce pain without increasing the vascular complications.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to reducing ambulation time, changing patients’ position during immobilization was also proposed by previous research [ 3 , 8 , 19 ]. Two studies [ 3 , 19 ] found that position change to a semi-seated position 2 h after TFA is effective and safe to reduce pain without increasing the vascular complications. Though many previous studies have demonstrated the benefits of early ambulation or position change, most protocols are single with the lack of systematization and wholeness (focused on early ambulation or position change only), and multiple interventions are generated based on experiences rather than scientific evidence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of bleeding and urine incontinence, there are still no changes that occur in both groups. The conclusion of their research says positioning patient in a semi-seated position following TFA decreases pain effectively and safely without worsening circulatory problems [34].…”
Section: -Hojjat Et Al (2021)mentioning
confidence: 99%